Integrating Daʿwah into Arabic Pedagogy for Society 5.0: Classroom ‎Innovations - Zulhannan; Umi Mahmudah; Umi Musyarofah (JPI: Jurnal Pustaka Indonesia, 2025)
This article aims to formulate and test the integration of daʿwah values—ḥikmah (prudential wisdom), mauʿiẓah ḥasanah (ethical exhortation), and courteous dialogic engagement—into Arabic pedagogy to meet the demands of Society 5.0, thereby aligning linguistic competence with character formation and technological literacy. Adopting a design-based research approach across multiple cycles of design–implementation–reflection in university-level Arabic classes, the study combines task-based and project-based learning, micro-scale service-learning, reflective Arabic dialogues, and AI-mediated feedback. Data were gathered from classroom observations, student artifacts, pre/post assessments of communicative performance, and brief attitudinal surveys; analyses employed thematic coding and descriptive statistics to iteratively refine each cycle’s design. Findings indicate gains in communicative accuracy and pragmatic appropriateness, heightened learner engagement, and clearer transfer from classroom discourse to community-oriented action; lecturers reported stronger alignment between linguistic outcomes and character education, while students demonstrated more orderly and ethical argumentation in Arabic. The study concludes that a daʿwah-informed framework operationalizes Arabic as a vehicle for ethically grounded communication suited to the digital-human ecosystem of Society 5.0, offering replicable classroom routines and assessment rubrics for higher-education contexts.